Partisipasi Kerja Disabilitas pada Sektor Informal di Pulau Jawa Tahun 2021 - Sirait, Finer Mayland; Rahani, Rini (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Persons with disabilities are vulnerable group and often face challenges in accessing inclusive and equal employment. Most persons with disabilities work in informal sector which identic with the absence of guaranteed work contracts, guaranteed wages, guaranteed pensions, health insurance and other benefits. This condition was increasingly not ideal during the COVID-19 pandemic related to the 2021 Imposition of Restrictions on Community Activities (PPKM) policy. This study aimed to find out the general description and prevalence of workers with disabilities based on the work sector, examine the influence and tendency of individual and regional variable categories on the persons with disabilities participation in the informal sector in Java in 2021 using a multilevel logistic regression model. The data used was the August 2021 Sakernas raw data and publications of Ministry of National Development Planning and the National Commission on Disabilities. Results showed that multilevel binary logistic regression fitted for modelling the individual and regional variables effect on the work participation of persons with disabilities in informal sector. Individual variables (gender, age, highest education, and job training) and regional variables (the Employment to Population Ratio (EPR) of persons with disabilities) significantly affected the participation of persons with disabilities in the informal sector.